A influência do tabagismo na infecção por HPV no desenvolvimento do câncer de pênis: estudos clínicos - ABREU, Ana Paula de Araújo (2020)
Tobacco smoking and HPV infection are considered risk factors for penile cancer development, a rare neoplasia that, in the state of Maranhão, has a high incidence. Besides that, genetic factors might make the population of Maranhão more susceptible to the development of cancers, like the deletion of GSTM1 and GSTT1 genes, which are involved in cellular detoxification, including cigarette compounds. Thereby, this work is justified by the need for understanding of the impact of tobacco smoking, the deletion of GSTM1 and GSTT1 genes and HPV infection in the development of penile cancer. The objective was the analysis of the relation between the smoking and the HPV infection in the development of penile cancer. This is an analytical, qualitative, retrospective and cross-sectional epidemiological study, of a historical series of epidermoid penile carcinomas, which used 55 penile tumor samples stored in the Tumor and DNA Biobank – “Biobanco de Tumores e DNA do Maranhão” (BTMA). Sociodemographic data was obtained by means of a questionnaire, clinical and histopathologic data were collected from the medical record.The genomic DNA of the samples was extracted then Nested Polymerase Chain Reaction (Nested PCR) was executed for the detection of HPV using PGMY and GP+ primers, and then agarose gel electrophoresis was executed. Positive samples were sequenced by Sanger method for the identification of the virus type. In order to analyse the deletion of GSTM1 and GSTT1 gene, conventional PCR was used, followed by the agarose gel electrophoresis. It was observed that most of the patients were men above 60 years old (63.6%), from interior of Maranhão state (60%), they were smokers or former smokers (65.5%), carriers of HPV (74.5%), being most frequently the high-risk oncogenic HPV (41.4%), and from those, 64.7% were subtype 16. Most research subjects had ulcerated lesions of the epidermoid histological type and usual subtype. Regarding the TNM staging, it was observed a predominance of higher tumor stages, II and III (61.8%). HPV patients and those exposed to tobacco tend to present with higher stages (52.9%). The subjects that presented deletion in their GSTT1 and/or GSTM1 genes presented TNM stages II and III (54.2%), mostly in the combination GSTT1+/GSTM1null (41.7%), with statistically significant p=0.012. In conclusion, tobacco smoking is associated to penile cancer and exerts influence in the tumor stage on patients that are also HPV patients. More extensive studies should be carried out in order to narrow this association, as well as, improve the understanding of the interference mechanisms of tobacco smoking on tumor progression and the influence of this practice on the GSTT1 and GSTM1 genes.